Teaching BSW Students to Apply the Grand Challenges in Social Work Through Field-Based Research Projects. Issue 2 (15th March 2023) - Jacob, Anupama; Bentley, Kia J.
ABSTRACT: The long-recognized disconnect between research and practice is reflected by social work students who often report significant apprehension about their research classes, likely at least in part because of a poor understanding of the research–practice interface and an unfamiliarity with larger professional social change initiatives like the Grand Challenges for Social Work. To counter this disconnect, this study showcases a successful model for BSW research courses that provides students with opportunities to engage in practice-informed research and research-informed practice through original, empirical, student-led, field-based research projects that are explicitly applied to the Grand Challenges. Drawing on student reflections, the study provides a useful exemplar of how a BSW research course can shape students' understanding of the role of research in practice that supports the even larger goal of contributing to the profession's impact on social problems and its role in social change.